Diphenyl ether based receptors for chemical sensing of Iron(III) using Spectrofluorimetry - Kaur, Gagandeep (My University, 2014)
Diphenyl ether based receptor was synthesised and used as a chemical sensor for iron(III).The ion-recognition studies of receptor (DPE-I) has been studied through UV-Vis and Fluorescence spectroscopies. The proposed sensor has been studied for interference from metal ions. No interference was observed from metal ions like Na+, K+, Mg2+, Cu2+, Ba2+, Cr3+,Co2+, Ni2+, Zn2+, Hg2+, Cd2+, and Pb2+. The chemical sensor shows linear response in concentration range 10- 4 to 10- 3M of Iron (III) ions. The lower detection limit is 4.23 x 10-4 M. Job’s plot analysis showed its 1:1 complexation with Fe3+. Optimization of receptor was done by theoretical studies using GAUSSIAN 03W software receptor with iron (III) in their energy minimization state. The results supported the experimental observation.
Master of Science-Chemistry-Dissertation
Keywords: Synthesis of diphenylethers; UV-visible; fluerescence; theoretical studies; chemistry; biochemistry